The Role of Self-Efficacy as a Moderator of the Determining Factors of Entrepreneurial Intention - Ida Puspitowati; Tri Widayati (LPPM Universitas PGRI Sumatera Barat, 2024)
Entrepreneurship plays a crucial role in driving economic growth, innovation, and employment generation, especially in developing countries like Indonesia. This study examines the determinants of entrepreneurial intention (IB) among undergraduate students at four private universities in West Jakarta—Universitas Tarumanagara, Universitas Bina Nusantara, Universitas Podomoro, and Universitas Trisakti—using the Theory of Planned Behavior (TPB) as the theoretical framework. The research specifically investigates the effects of entrepreneurial education (PK), perceived behavioral control (PBC), and adversity quotient (KA) on entrepreneurial intention, while also testing the moderating role of entrepreneurial self-efficacy (ED). Data were collected through an online questionnaire from 210 respondents who had taken entrepreneurship courses, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results demonstrate that entrepreneurial education and perceived behavioral control are the strongest predictors of entrepreneurial intention, explaining 71.7–72.4% of its variance. Results of this research, shows that entrepreneurial self-efficacy is significantly moderating effects of strengthening the relationship between adversity quotient and intention while reducing the marginal impact of education among highly confident students. Overall, the findings extend the TPB by incorporating both psychological and sociocultural dimensions, highlighting that entrepreneurial intention formation is shaped not only by knowledge and perceived capability but also by confidence and contextual differences. The study recommends integrating experiential, gender-inclusive, and resilience-based approaches into entrepreneurship education to foster stronger entrepreneurial mindsets among university students